Depression and Personality Traits - Pérez- Pacheco, Yary Zulay J (Mexican Journal of Medical Research ICSA, 2018)
Temperament is a risk factor for major depressive disorder, more specifically neuroticism or negative emotionality and it seems that higher levels makes the subjects more likely to develop depressive episodes in response to stressful life events. The objective of this review is to establish those personality traits that are most related to depression. From all the articles, seven of them are about the high levels of neuroticism and low levels of extroversion in depressive patients, this for the theory of the five factors. On the other hand, the studies based on the Cloninger theory talk about high levels of damage avoidance and low levels of self-directivity that are related to the presentation of the disorder. Regardless of the theory used, it becomes evident the need to interrogate personality traits in psychiatric and healthy patients, in the latter for the prevention of disorders.